Strategi Pengembangan UMKM Melalui Geo-Biz Project dan Pembuatan Laporan Laba Rugi di Wilayah Kampung Bharu, Malaysia - Vanny Wulan Sari; Dian Hermawan; Rizky Titis Agustianto; Endang Silaningsih; Erni Yuningsih; Sri Harini; Tini Kartini (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
MSMEs are one of the drivers of a country’s economic engine. In this context, the empowerment of MSMEs is continuously pursued to optimize community production outcomes and improve community welfare. The purpose of this study is to empower MSMEs in managing their finances as well as to provide convenience in interacting with customers through digital media. The medium used is Geo-Biz. The method applied is community service conducted in Kampung Bharu, Malaysia. The results of the activity show that MSME development has become one of the government’s priorities, leading to two flagship programs: a promotion strategy using Geo-Biz and assistance in preparing income statements that the community can utilize to manage their businesses.